PENGUJIAN MARKET OVERREACTION PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA - Cut Lisa, Syarifah Rahmawati (Departemen Manajemen, 2018)
This research aimed to test the existence of a market overreaction in the Indonesia Stock Exchange (BEI). Samples in research are go public companies in Indonesia Stock Exchange during the period of 2012-2016. Tests using monthly closing price data. This research classifies winner and loser portfolios into three sizes of large, medium, and small. Result obtained by using paired sample t-test shows that there has been a price reversal between the period of formation and observed on all sizes, either large, medium, or small. The loser stock in the formation period turned into winner stock in the observed period, and the winner stock in the formation period turned into loser stock in the observed period. This result is an indicator occurence of market overreaction in Indonesia Stock Exchange. Strictly, the results of this study conclude that there is a market overreaction on the company go public on the Indonesia Stock Exchange, either on large, medium, or small. Therefore, contrarian strategy can be applied in Indonesia Stock Exchange.